High voltage engineering : fundamentals - Kuffel, E. (Butterworth-Heinemann, 2000)
Power transfer for large systems depends on high system voltages. The basics of high voltage laboratory techniques and phenomena, together with the principles governing the design of high voltage insulation.A classic text on high voltage engineeringEntirely revised to bring you up-to-date with current practiceBenefit from expanded sections on testing and diagnostic techniques
Description based upon print version of record.
Keywords: Electrical engineering.; High voltages.; Electric insulators and insulation.; Breakdown (Electricity)